Does Psychological Empowerment Mediate the Impact of Transformational Leadership Style on Employee Performance: Evidence from the Public Sector in Jaffna District - Raveendran, T.; Gamage, A.S. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2021)
Sri Lankans continue to rely on public service to satisfy most of their needs, however, they are increasingly distrustful of its performance. If the managers and leaders better manage the employees, it is possible to move toward a productive workforce and to meet the common expectations of the people. There is a need to adopt appropriate style in order to promote psychological empowerment among employees and to improve employee performance. In the Sri Lankan public sector, it is very rare to come across studies which have been conducted on the impact of leadership style on employees’ performance, particularly in the Northern Province. Thus, the current study aims to examine the association between transformational leadership style and employees’ job performance and the potential mediating effect of psychological empowerment in the effect of transformational leadership on employee performance in the public sector organizations in Jaffna District. The study employed survey method and 287 employees participated in this study. Leadership style was measured using MLQ Rater Form 5-x, employee performance was measured using Job Performance Scale and psychological empowerment was measured using Empowerment Scale. Exploratory factor analysis was performed to get factor structure and confirmatory factor analysis was performed to confirm the validity and reliability of the study instruments. The results revealed that transformational leadership has a positive impact on job performance and on psychological empowerment. It was also found that psychological empowerment has a mediating effect in the impact of transformational leadership on employee performance. This study recommends that the leaders should pay more attention in their leadership style as a way to improve employee performance. This study further suggests that future researchers should cover other public sector organizations to better understand the relationship between the variables.
Keywords: Public sector, job performance, psychological empowerment and transformational leadership